Buckle removal in retinal detachment surgery: a consecutive caseseries - Nuzzi, G.; Rossi, S. (Acta Biomedica Atenei Parmensis, 2008)
Purpose: To evaluate the outcome after buckle removal in a consecutive series of treated detachments. Methods: Segmental and/or encircling buckles were removed in 46 consecutive patients operated upon for rhegmatogenous retinal detachment, showing buckle extrusion, recurrent pain, and diplopia. Patients underwent a preoperative retinal examination, and a six- months postoperative follow-up. Results: Cryopexy of retinal breaks was performed in all 46 patients during the primary surgery. At the time of buckle removal none of the patients underwent argon-laser treatment. The removed buckling material was made of miragel®  in 32 cases (74%), silicone sponge in 7 (17%), and silicone band in 4 (9%). The time between the first surgery and buckle removal ranged from 1 to 17 years (8±7.5, M±SD). Neither postoperative complications, nor recurrences of retinal detachment developed. Best corrected visual acuity remained unchanged during the follow-up. Diplopia resolved in all 4 eyes after buckle removal with no need for a strabismus operation, prismatic lenses were required in one case only. Conclusions: Although the absence of a control group, the adequately applied retinopexy during primary surgery could probably prevent the recurrence of retinal detachment.